Strategi Pembelajaran bahasa yang efektif: Antara Kompetensi, Produksi, dan Pembentukan Kemampuan - Siti Nur Sofirotul Jannah; Alfi Manzilatur Rokhmah; M Yunus Abu Bakar (JURNAL ILMIAH NUSANTARA, 2025)
Language learning encompasses various complex aspects, one of which is the mastery of key issues such as competence and performance, comprehension and production, as well as the debate between nature and nurture in language acquisition. This article provides a detailed discussion on how these aspects play a role in the learning process and explores strategies that can be used to develop and strengthen them. This study is supported by various theoretical references and research findings in the fields of applied linguistics and language education.